Three-dimensional multilayer cylindrical tunnel model for calculating train-induced dynamic stress in saturated soils. (December 2016) - Di, Honggui; Zhou, Shunhua; He, Chao; Zhang, Xiaohui; Luo, Zhe
Abstract: This study proposes an improved tunnel model for evaluating train-induced dynamic stress in saturated soils, which can consider multiple moving loads, grouting layer and pore-water pressure. Using Shanghai Metro's actual parameters for train speed, tunnel, grouting layer and soils, the analysis of the spatial distribution of dynamic stress for soils and stress state of various locations under moving train loads shows that neglecting effects such as pore-water pressure can lead to underestimating dynamic normal stress and overestimating dynamic shear stress in the soils below tunnel. This model can be further extended to investigate principal stress axes rotations and tunnel settlement.